2021
DOI: 10.1155/2021/8976625
|View full text |Cite|
|
Sign up to set email alerts
|

Changes of Multisectoral Collaboration and Service Delivery in Hypertension Prevention and Control before and after the 2009 New Healthcare Reform in China: An Interrupted Time-Series Study

Abstract: Objectives. There is a need to assess the 2009 new healthcare reform in China on hypertension prevention. It helps to control from the perspectives of multisectoral participation, government responsibility assignment, performance assessment, and service delivery. Design. Interrupted time-series study. Setting. 31 provinces in mainland China. Primary and Secondary Outcome Measures. Based on the content analysis of publicly available policy documents from 31 provinces regarding hypertension prevention and contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…The WHO recommends countries use operational indicators such as treatment coverage to facilitate implementation of PHS (3). Therefore, we designed the indicator Assessable Healthcare Service Coverage Rate (ASCR) (25) to indicate the degree of attention to the quality of service delivery, which can be measured by the proportion of service types with evaluable indicators in PHS. We assumed that a high value of the ASCR indicated that PHS could be provided more effectively than a low value of the ASCR.…”
Section: Indicator Designmentioning
confidence: 99%
“…The WHO recommends countries use operational indicators such as treatment coverage to facilitate implementation of PHS (3). Therefore, we designed the indicator Assessable Healthcare Service Coverage Rate (ASCR) (25) to indicate the degree of attention to the quality of service delivery, which can be measured by the proportion of service types with evaluable indicators in PHS. We assumed that a high value of the ASCR indicated that PHS could be provided more effectively than a low value of the ASCR.…”
Section: Indicator Designmentioning
confidence: 99%
“…Journal of Healthcare Engineering has retracted the article titled “Changes of Multisectoral Collaboration and Service Delivery in Hypertension Prevention and Control before and after the 2009 New Healthcare Reform in China: An Interrupted Time-Series Study” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%